Vertical Ties Across Borders: Do Japanese Production Networks Jeopardize Competitive Markets in Southeast Asia? - Walter Hatch (Washington University Global Studies Law Review, 2002)
In this Article, I strive to fill part of the void in the academic literature by carefully considering the impact of vertical integration and quasi-integration via foreign direct investment (FDI) on markets in developing economies. More specifically, I ask the following question: under what conditions are MNCs able to use vertical restraints-particularly exclusionary supply and distribution arrangements-to raise entry costs for prospective competitors, thereby securing dominant positions in host country markets?
Keywords: Japan; Multinational corporations; Vertical integration; Foreign direct investment